Indian Literature and the World Multilingualism, Translation, and the Public Sphere - Ciocca, Rossella; Srivastava, Neelam (Springer Nature, 2017)
Moves beyond restrictive Anglocentric approaches Features contributions from a spectrum of academics, from early career researchers to key names in the fieldAddresses areas such as translation studies as well as postcolonial studies and world literature